The Joy Luck Club - Tsai Chin.; Chinh, Kieu.; Lu, Lisa.; Nuyen, France 1939-.; Chao, Rosalind; Tom, Lauren; Tomita, Tamlyn; Wen, Ming-Na.; Stone, Oliver; Tan, Amy.; Wang, Wayne; Hollywood Pictures (Quezon City Viva Video, 1999)
Follows the story of four lifelong friends, whose lives are filled with joy and heartbreak, and shows how their experiences have affected the hopes and dreams they hold for each of their children.
VHS ; hi-fi, Dolby surround stereo
Based on the novel by Amy Tan.
Originally released as VHS by Buena Vista Home Entertainment, Inc. in 1994 and as motion picture in 1993.
Music, Rachel Portman ; director of photography, Amir Mokri ; executive producers, Oliver Stone, Janet Yang ; screenplay, Amy Tan & Ronald Bass ; producers, Wayne Wang, Amy Tan, Ronald Bass, Patrick Markey ; edited by Maysie Hoy.
Tsai Chin, Kieu Chinh, Lisa Lu, France Nuyen, Rosalind Chao, Lauren Tom, Tamlyn Tomita, Ming-Na Wen, Michael Paul Chan, Andrew McCarthy, Christopher Rich, Russell Wong, Vivian Wu
Rated R.
Keywords: Mothers and daughters -- Drama; Infanticide -- China; Chinese American families -- Drama; Chinese American women; Film adaptations; Feature films; Infanticide